1999
DOI: 10.1053/joca.1998.0208
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type VI collagen in normal and osteoarthritic human cartilage

Abstract: These results demonstrate that in normal and osteoarthritic cartilage, type VI collagen is expressed in a zone specific pattern. The observed increase of type VI collagen expression in osteoarthritis suggests a potential role in the disease process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 40 publications
6
42
0
3
Order By: Relevance
“…(J Histochem Cytochem 57:923-931, 2009) K E Y W O R D S osteoarthritis cartilage ER stress bag-1 grp78 collagen VI NG2 OSTEOARTHRITIS (OA) IS A PROGRESSIVE DISEASE, with changes in chondrocyte gene expression and extracellular matrix (ECM) composition occurring before macroscopic structural damage is observed (Hamerman 1989). Articular chondrocytes in OA exhibit a hypermetabolic phenotype, with studies describing highly proliferative clonal chondrocytes, along with the upand downregulation of ECM molecules such as aggrecan (Matyas et al 1995), collagen II (Matyas et al 1995), perlecan (Tesche and Miosge 2004), metalloproteases (Mitchell et al 1996;Reboul et al 1996;Billinghurst et al 1997), aggrecanases (Lark et al 1997;Naito et al 2007), fibronectin (Wurster and Lust 1984;Brown and Jones 1990), collagen I (Deshmukh and Root 1974), and collagen VI (Hambach et al 1998;Pullig et al 1999). Etiologies ranging from genetic inheritance to trauma and aging can all contribute to the onset of OA, and further changes in gene expression occur as the disease progresses (Hardingham 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(J Histochem Cytochem 57:923-931, 2009) K E Y W O R D S osteoarthritis cartilage ER stress bag-1 grp78 collagen VI NG2 OSTEOARTHRITIS (OA) IS A PROGRESSIVE DISEASE, with changes in chondrocyte gene expression and extracellular matrix (ECM) composition occurring before macroscopic structural damage is observed (Hamerman 1989). Articular chondrocytes in OA exhibit a hypermetabolic phenotype, with studies describing highly proliferative clonal chondrocytes, along with the upand downregulation of ECM molecules such as aggrecan (Matyas et al 1995), collagen II (Matyas et al 1995), perlecan (Tesche and Miosge 2004), metalloproteases (Mitchell et al 1996;Reboul et al 1996;Billinghurst et al 1997), aggrecanases (Lark et al 1997;Naito et al 2007), fibronectin (Wurster and Lust 1984;Brown and Jones 1990), collagen I (Deshmukh and Root 1974), and collagen VI (Hambach et al 1998;Pullig et al 1999). Etiologies ranging from genetic inheritance to trauma and aging can all contribute to the onset of OA, and further changes in gene expression occur as the disease progresses (Hardingham 2008).…”
mentioning
confidence: 99%
“…A number of ECM molecules have been reported to be localized to the pericellular matrix, including the network-forming collagen type VI, which is a vital component of both ECM signaling and cell-matrix structural stability (Poole 1997;Alexopoulos et al 2005;Guilak et al 2006). Collagen VI has been reported to increase expression in osteoarthritic cartilage, and to lose its peri-cellular localization (Hambach et al 1998;Pullig et al 1999;Söder et al 2002). As with other secreted collagens, type VI is modified and assembled within the ER (Sipila et al 2007).…”
mentioning
confidence: 99%
“…Besides the major ECM components, the expression of type VI collagen was also investigated in all three experimental groups. This minor protein seems to play an important role for the integrity of the cartilage matrix by anchoring chondrocytes to their surrounding matrix 44 . Under normal conditions, this protein occurs primarily in the pericellular matrix that surrounds the chondrocytes throughout the different zones.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaline cartilage contains a relatively low content of type VI collagen (less than 2% of all articular cartilage tissue collagens) that is found in all cartilage zones within the pericellular regions around chondrocytes (Pullig et al, 1999). Type VI collagen molecules are of heterotrimeric organization as they are composed of three non-identical alpha chains.…”
Section: Collagen VImentioning
confidence: 99%
“…It has been previously demonstrated that type VI collagen content is increased in certain patients suffering from OA. However, it is suspected that disregulated tissue homeostasis causes excessive collagen anabolism and deposition (Pullig et al, 1999). Mutations in the genes that code for the three type VI collagen alpha chains have been associated with noncartilagespecific abnormalities such as muscular dystrophy (Pace et al, 2008) and Bethlem myopathy (Lamandé et al, 1998).…”
Section: Collagen VImentioning
confidence: 99%